Joseph Campbell: trajetórias, mitologias, ressonâncias - Silva, Carlos Aldemir Farias da (2012)
As immemorial reserves of the human condition, the myths are present in all societies. They organize cosmovisions, propose solutions to dilemmas, enigmas and contradictions that the real world cannot solve. As machines of time suppression, as defined by Claude Lévi-Strauss, the mythic narratives do not submit themselves to the linearity of history. Joseph Campbell (1904-1987), centerpiece of this thesis, a north-american born in New York, occupies a place of great remark in the pantheon of mythological interpretations. The greatness of his work is more than recognized, although the comprehension of his ideas still remains shy in Human Sciences. It is a body of work that is open to the various cultural devices which, beyond science, include literature and cinema, the latter being responsible for the popularization of Campbell‟s ideas with the Star Wars series. The thesis invests in the life and work dialogism from a bibliographic incursion; it traces the most representative itineraries of Campbell‟s life (Stephen and Robin Larsen) which led him to discuss the functions and potentialities of myth in contemporary society; it sketches the scenery of science in the interior from which emerges the north-american mythologist; it exposes a synthetic archaeology of the figures which constitute The Hero of a Thousand Faces; it exposes the author‟s arguments concerning his treatment of the recurring themes in mythical narratives (cultural diversity) towards the universality of culture (archetypical unity of the myths); it presents the chronological mapping of the author‟s work in the original editions in English and its translations in Brazil; it exposes and problematizes stemming from the research on the Thesis‟ Database of Capes the resonance of Campbell‟s ideas in the Brazilian scientific production (1990-2010); and it presents, in full, interviews with two experts and translators of the author‟s works to Portuguese. The central argument of this thesis is the indissoluble relationship between the author‟s lived experience and interest for the study of myths, that is, the contingencies of life which illuminate the choice of a study theme, above all those which are rooted in infancy and adolescence. Because he is a transdisciplinary thinker who moved in the dominions of art, literature, science and religion, the polyphony contained in his compared study of world mythologies demanded, from this research, a dialogue with authors from different and complementary areas like Carl Gustav Jung, Jean-Pierre Vernant, Edgar Morin among others. The basic interpretative soil centered on nineteen fundamental works translated in Brazil. The thesis has as a horizon to establish connections between science and arts, towards the constitution of a fundamental anthropology of universalist, complex and transdisciplinary base